2016
DOI: 10.1093/scan/nsw146
|View full text |Cite
|
Sign up to set email alerts
|

Increased neural responses to empathy for pain might explain how acute stress increases prosociality

Abstract: Recent behavioral investigations suggest that acute stress can increase prosocial behavior. Here, we investigated whether increased empathy represents a potential mechanism for this finding. Using functional magnetic resonance imaging, we assessed the effects of acute stress on neural responses related to automatic and regulatory components of empathy for pain as well as subsequent prosocial behavior. Stress increased activation in brain areas associated with the automatic sharing of others’ pain, such as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 37 publications
9
86
0
Order By: Relevance
“…The present findings might also relate to prior research showing that stress increased the magnitude of responding in "empathy for pain" brain regions in response to seeing someone else in pain 8 . A potential common mechanism that could relate our present findings to these prior results might be that under stress, individuals become more other-oriented, which increases empathy for others and also valuation of others' rewards.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The present findings might also relate to prior research showing that stress increased the magnitude of responding in "empathy for pain" brain regions in response to seeing someone else in pain 8 . A potential common mechanism that could relate our present findings to these prior results might be that under stress, individuals become more other-oriented, which increases empathy for others and also valuation of others' rewards.…”
Section: Discussionsupporting
confidence: 81%
“…This would be in line with converging evidence from behavioral research indicating that stress increases prosocial behavior [1][2][3][4][5][6] , which has been interpreted in light of the "tend-and-befriend" hypothesis stating that individuals become more prosocial under stress in order to secure help from others 7 . Furthermore, previous research has shown that stress increases the magnitude of brain activity in empathy for pain areas when viewing others in pain which predicted later prosocial behavior 8 . The results of the present study extend this research by showing that in the domain of value computation, stress leads to an increased differentiation between high and low value for others suggesting that stressed individuals track the potential reward for others more closely.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations